Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1088/0004-637x/755/1/57
|View full text |Cite
|
Sign up to set email alerts
|

HERSCHEL-PACS OBSERVATIONS OF FAR-IR CO LINE EMISSION IN NGC 1068: HIGHLY EXCITED MOLECULAR GAS IN THE CIRCUMNUCLEAR DISK

Abstract: We report the detection of far-IR CO rotational emission from the prototypical Seyfert 2 galaxy NGC 1068. Using Herschel-PACS, we have detected 11 transitions in the J upper = 14 − 30 (E upper /k B = 580 − 2565 K) range, all of which are consistent with arising from within the central 10 ′′ (700 pc). The detected transitions are modeled as arising from 2 different components: a moderate excitation (ME) component close to the galaxy systemic velocity, and a high excitation (HE) component that is blueshifted by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 96 publications
(208 reference statements)
5
92
0
Order By: Relevance
“…We tried to fit CO ladders in the central 45 with a single LVG component first, however, it does not produce a good fit. This is not surprising since the modeling results in previous studies (e.g., Kamenetzky et al 2012;Hailey-Dunsheath et al 2012;Rigopoulou et al 2013) have shown that the coexistence of multiple excitation gas components in nearby galaxies (also see Lu et al 2014). Therefore, we use two LVG components to model the gas excitation in the central 45 region.…”
Section: Two-component Modeling In the Central 45 Regionmentioning
confidence: 58%
See 2 more Smart Citations
“…We tried to fit CO ladders in the central 45 with a single LVG component first, however, it does not produce a good fit. This is not surprising since the modeling results in previous studies (e.g., Kamenetzky et al 2012;Hailey-Dunsheath et al 2012;Rigopoulou et al 2013) have shown that the coexistence of multiple excitation gas components in nearby galaxies (also see Lu et al 2014). Therefore, we use two LVG components to model the gas excitation in the central 45 region.…”
Section: Two-component Modeling In the Central 45 Regionmentioning
confidence: 58%
“…Although Circinus has a much smaller distance (∼4 Mpc) than NGC 1068 (∼14.4 Mpc Bland-Hawthorn et al 1997), the angular sizes of the gas-rich region in these two galaxies are both about 40 (in diameter). Both of them have strong S-F activities in their centers, and are fed by large amounts of molecular material (e.g., Curran et al 2001;Hailey-Dunsheath et al 2012).…”
Section: Comparison With Ngc 1068mentioning
confidence: 99%
See 1 more Smart Citation
“…Usero et al 2004;Israel 2009;Kamenetzky et al 2011;Hailey-Dunsheath et al 2012;Aladro et al 2013). Interferometric observations of CO, as well as HCN, HCO + , CS, and SiO (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with ground-based telescope data, Photodector Array Camera and Spectrometer (PACS; Poglitsch et al 2010), Spectral and Photometric Imaging Receiver (SPIRE; Griffin et al 2010), and Heterodyne Instrument for the Far Infrared (HIFI; de Graauw et al 2010) spectroscopic observations have enabled us to construct CO spectral line energy distributions (SLEDs) from the upper level J u = 1 to 50. In the past several years, Herschel-based CO SLEDs have been extensively examined for a wide range of Galactic (e.g., photodissociation regions (PDRs): Habart et al 2010;Köhler et al 2014;Pon et al 2014;Stock et al 2015;protostars: Larson et al 2015) and extragalactic sources (e.g., infrared (IR)-bright galaxies: Rangwala et al 2011;Kamenetzky et al 2012;Meijerink et al 2013;Pellegrini et al 2013;Greve et al 2014;Lu et al 2014;Papadopoulos et al 2014;Rosenberg et al 2014;Schirm et al 2014;Mashian et al 2015;Wu et al 2015b; Seyfert galaxies: van der Werf et al 2010;Hailey-Dunsheath et al 2012;Israel et al 2014), revealing the ubiquitous presence of warm molecular gas (T k 100 K). Various heating sources, e.g., ultraviolet (UV) photons, X-rays, and cosmic-rays, have been invoked to explain the properties of this warm molecular gas and the emerging picture is that non-ionizing sources such as mechanical heating (e.g., shocks driven by merging activities, stellar winds, and supernova explosions) must play a critical role.…”
mentioning
confidence: 99%